Prevalence and factors associated with short birth interval in the semi-rural community of Kaya, Burkina Faso: results of a community-based survey - Abou Coulibaly; Adama Baguiya; Ivlabèhirè Bertrand Meda; Tiéba Millogo; Aristide Marie Arsène Koumbem; Franck Garanet; Seni Kouanda (BMC, 2024)
Abstract Background A short birth interval adversely affects the health of mothers and children. This study aimed to measure the prevalence of short birth intervals and identify their associated factors in a semi-urban setting in Burkina Faso. Methods We conducted a cross-sectional study in which data were collected in households between May and October 2022. The dependent variable was the short birth interval (SBI), defined by the World Health Organization as the time between two live births. We performed a multilevel mixed-effects Poisson regression with robust variance to determine the factors associated with the SBI by reporting adjusted prevalence ratios (aPR) with a 95% confidence interval (CI). Results A total of 5544 birth intervals were recorded from 4067 women. A short birth interval was found in 1503 cases out of 5544, i.e., a frequency of 27.1%. The prevalence of short birth interval (time between two live births less than 33 months) was higher in never users of modern contraceptive users (aPR = 1.24; 95% CI [1.14-1.34] vs. previous users), in younger ages with aPR of 4.21 (95% CI [3.30-5.37]), 2.47 (95% CI [1.96-3.11]), and 1.45 (95% CI [1.16-1.81]), respectively for under 18, 18-24 years old, and 25-34 years old, compared to 35 and over. Childbirths occurring before the implementation of the maternal and infant free health care policy (aPR = 2.13; 95% CI [1.98-2.30]) and also before the free family planning policy (aPR = 1.53; 95% CI [1.28-1.81]) were more likely to have SBI. Women with low socio-economic positions were also more likely to have SBI. Conclusion This study found a high SBI in Burkina Faso (more than one woman out of four). Our results have programmatic implications, as some factors, such as contraceptive practice and socioeconomic status, are modifiable. These factors need particular attention to lengthen birth intervals and, in turn, improve mother-child couple health by reducing short birth interval consequences.